Journey to Beatrice (Johns Hopkins University Press, 2019)
Originally published in 1977. This volume recovers the allegory in Dante's Divine Comedy and presumes that readers' deficient knowledge of or interest in allegory have led to misinterpretations of Dante's poem. None of the dozens of commentaries on the Comedy published in the first half of the twentieth century was concerned with allegory more than sporadically, says Singleton, and so these treatments directed readers' attention to the merest disjecta membra of that continuous dimension of the poem. From Singleton's perspective, the allegory of the Comedy is an imitation of Biblical allegory, which was acknowledged by thinkers in the Middle Ages but not by intellectuals during and following the Renaissance. Singleton attempts to restore the allegorical elements to the foreground of interpreting the Comedy.